2022
DOI: 10.3390/jmse10121804
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Design and Experimental Research on a Bionic Crab Robot with Amphibious Multi-Modal Movement

Abstract: Bionic amphibious robots are the intersection of biology and robotics; they have the advantages of environmental adaptability and maneuverability. An amphibious robot that combines walking and swimming move modes inspired by a crab (Portunus) is presented in this article. The outstanding characteristic of the robot is that its environmental adaptability relies on the bionic multi-modal movement, which is based on two modular bionic swimming legs and six modular walking legs. We designed the biomimetic crab rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In previous studies, we examined the crab-like robot's underwater bounding gait [18], swimming paddle design and flapping trajectory [39], and the effects of leg mechanism kinematic modeling and swimming paddle structural parameters on hydrodynamics [40], and demonstrated that the crab-like robot has good mobility capabilities in an amphibious environment. This paper presents a relevant study on the impact of bionic shell attitude change on lift and drag, which is utilized to optimize the underwater motion attitude of the crab-like robot, thereby establishing a research foundation for the promotion and autonomous motion control of crab-like robots.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we examined the crab-like robot's underwater bounding gait [18], swimming paddle design and flapping trajectory [39], and the effects of leg mechanism kinematic modeling and swimming paddle structural parameters on hydrodynamics [40], and demonstrated that the crab-like robot has good mobility capabilities in an amphibious environment. This paper presents a relevant study on the impact of bionic shell attitude change on lift and drag, which is utilized to optimize the underwater motion attitude of the crab-like robot, thereby establishing a research foundation for the promotion and autonomous motion control of crab-like robots.…”
Section: Introductionmentioning
confidence: 99%
“…Robots can walk straight, walk laterally, turn in place on land, swim, and jump underwater. Previous studies investigated the design principles and gait experimental results of the undersea propulsion mode of a crab-like robot called "crab bounding gait" [22], introducing the design of the swimming paddle of the imitation crablike robot with the swimming prize swimming simulation process [23] as well as swimming paddle structural parameters on hydrodynamics [24]. This research initiates by presenting the design and dynamics modeling process of the parallel leg structure for a crab-like robot, wherein the parallel leg structure outperformed the series leg structure in terms of load capacity.…”
Section: Introductionmentioning
confidence: 99%